A Revisit to the Impacts of Land Use Changes on the Human Wellbeing via Altering the Ecosystem Provisioning Services - Xiangzheng Deng; Zhihui Li; Jikun Huang; Qingling Shi; Yanfei Li (Advances in Meteorology)
It is widely acknowledged that land use changes (LUC) associated with climate variations are affecting the human wellbeing. This paper conducted a revisit to relevant researches on the impacts of LUC on human wellbeing via specifically altering the ecosystem provisioning services. First, the explorations on the influences of LUC on ecosystem provisioning services were reviewed, including the researches on the influences of LUC on agroecosystem services and forest and/or grassland ecosystem services. Then the quantitative identification of the impacts of LUC on ecosystem provisioning services was commented on. In the light of enhanced observation and valuation methods, several approaches to ecosystem services and improved models for assessing those ecosystem services were assessed. The major indicators used to uncover the influences of LUC on human wellbeing were summarized including the increase of inputs and the reduction of outputs in production and the augmented health risk induced by the irrational land uses. Finally, this paper uncovered the research gaps and proposed several research directions to address these gaps.